Labour Productivity during the Great Depression and the Great Recession in UK Engineering and Metal Manufacture - Robert A. Hart (Institute of Labor Economics (IZA), 2020)
This paper compares labour productivity during the Great Depression (GD) and the Great Recession (GR) in engineering, metal working and allied industries. Throughout, it distinguishes between output per worker and output per hour. From the peak-to-trough of the GD cycle, hourly labour productivity was countercyclical, remaining above its 1929 starting point. In the GR peak-to-trough period, hourly productivity was procyclical, falling below its 2007/08 starting point. While employment and average weekly hours reductions were much more pronounced in the GD compared to the GR, the GD recovery was both stronger and more sustained. The discussion of the different experiences in the two eras concentrates on employment and hours flexibility, the comparative lengths of weekly hours, the behaviour of real wages, and human capital aspects of labour inputs.
Keywords: E32; J23; J24; 330; labour productivity; Great Depression; Great Recession